O Papa Francisco e as mudanças na governança global da Igraja Católica - Faggioli, Massimo (Horizonte, 2021)
The article analyzes a few aspects of pope Francis’ governing style and the overall context for the issue of a synodal reform of the Catholic Church in the global world: the meaning of "Ecclesia semper reformanda" in a globalized Church; from episcopal collegiality to ecclesial synodality and the "synodal process 2021-2023; the relationship between pope Francis and the Roman Curia; the troubles with the globalization of the Church; the meaning of governance of the global Church in the age of the sexual abuse crisis. The article frames pope Francis’ most important decisions and choices for the governance of the Catholic Church in the most undisputable feature of the pontificate: the re-positioning out of a strictly European and North American theological and geopolitical axis, in order to embrace the global vocation of Catholicism. This implies some epoch-making shifts for what concerns the role of the Vatican, its relationship with the local churches and the bishops’ conferences, and the idea of church reform.